2010
DOI: 10.2353/ajpath.2010.100562
|View full text |Cite
|
Sign up to set email alerts
|

CD44 Deficiency Is Associated with Increased Bacterial Clearance but Enhanced Lung Inflammation During Gram-Negative Pneumonia

Abstract: Klebsiella pneumoniae is a frequently isolated causative pathogen in respiratory tract infections. CD44 is a transmembrane adhesion molecule that has been implicated in several immunological processes. To determine the role of CD44 during Klebsiella pneumonia, we intranasally infected wild-type and CD44 knockout (KO) mice with 10 2 to 10 4 colony-forming units of K. pneumoniae or administered Klebsiella lipopolysaccharide. During lethal infection, CD44 deficiency was associated with reduced bacterial growth an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 47 publications
1
23
0
Order By: Relevance
“…In CD44-deficient mice, there was an enhanced inflammatory response and neutrophil influx after exposure to E. coli. With the same mouse model, Van der Windt et al showed elevated hyaluronic acid levels, pulmonary inflammation, and edema for up to 10 days after infection with Klebsiella pneumoniae and S. pneumoniae (664,686). These investigators concluded that CD44 promotes the resolution of pneumonia, possibly through clearance of hyaluronic acid; hyaluronic acid can induce NF-B inflammatory pathways and inhibit the downregulation of Toll-like receptors (664,686).…”
Section: Bacterial Pneumonia and Other Infectionsmentioning
confidence: 97%
“…In CD44-deficient mice, there was an enhanced inflammatory response and neutrophil influx after exposure to E. coli. With the same mouse model, Van der Windt et al showed elevated hyaluronic acid levels, pulmonary inflammation, and edema for up to 10 days after infection with Klebsiella pneumoniae and S. pneumoniae (664,686). These investigators concluded that CD44 promotes the resolution of pneumonia, possibly through clearance of hyaluronic acid; hyaluronic acid can induce NF-B inflammatory pathways and inhibit the downregulation of Toll-like receptors (664,686).…”
Section: Bacterial Pneumonia and Other Infectionsmentioning
confidence: 97%
“…In mouse models, CD44 deficiency mice showed increased neutrophil accumulation in the lung and edema formation in Escherichia coli -induced pneumonia [145], but no difference was observed between these genotypes in Streptococcus pneumoniae -induced pneumonia [145]. CD44 deficiency is associated with increased bacterial clearance but enhanced lung inflammation in Klebsiella pneumonia -induced pneumonia [206]. …”
Section: Hyaluronan In Human Diseasesmentioning
confidence: 99%
“…Although AREG is known as epithelial cell-derived factor and recent studies show that AREG can be expressed by multiple populations of activated immune cells in inflammatory conditions [29]. In Host immune system, NFKB1 plays a major role in the activation of immune cells by upregulating the expression of many cytokines essential to the immune responses [30] and gene CD44 play important role in innate and adaptive immune responses, in the acute inflammatory response to both infectious and sterile stimuli and during infection CD44 may influence host defence by affecting phagocytosis [31] but in our study, we found that NFKB1 and CD44 are down regulated that means, MTB is burglarize and seizing the host immune system by slow down the expression of NFKB1. It has been reported that MET (Hepatocyte growth factor receptor) regulate various functions of immune cells, including differentiation and maturation, cytokine production, cellular migration and adhesion, and T cell effector function and HGF exerts anti-inflammatory activities through MET signaling [32].…”
Section: Some Beneficial Events With Respect To Host Cell Reverted Bymentioning
confidence: 99%